Assessing and treating conversations with partners in Parkinson's disease: A scoping review of the evidence. (4th July 2022) - Thilakaratne, Ramishka; Loftus, Andrea M.; Cocks, Naomi
Abstract: Purpose: This is a scoping review of the methods used in published research to assess conversations and the interventions used to treat conversations between people with Parkinson's disease and their partners. Communication partners were defined as significant others or next-of-kin. The aims were to describe the assessment methods and interventions used, and to identify gaps in the literature. Method: Four online databases were used to identify peer reviewed journal articles in English, which assess and/or treat conversations in this population. The titles and abstracts of the obtained articles were screened and irrelevant articles were excluded. The full texts of the remaining articles were read to determine which studies met the inclusion/exclusion criteria of this review. The methods used, conversational aspects assessed, the treatments conducted and outcome measures used, and the speech and language domains targeted were charted in order to examine the extent of the evidence to inform future research directions. Result: Eight studies met inclusion criteria. "Conversation analysis" was the most widely used method to assess conversations. These studies assessed conversational aspects relating to the domains of pragmatics, fluency, prosody and semantics. They highlighted the role of communication partners to support conversational interactions by using repair strategies during a communication breakdown. Only one study treated conversations by implementing communication partner training. Conclusion: The findings of this review emphasise gaps in the literature. It highlights the need for future research implementing communication partner training. There is also a need to assess conversation skills of partners in order to determine which strategies would be most effective to support their interaction. It highlights the importance of incorporating a participation-based approach to assessment and intervention involving all communication partners. This may lead to enhanced support for people with Parkinson's disease and their families, thus improving their quality of life.